The Catholic Monarchs on the Postage Stamps of Franco's Spain. - OLTRA, GUILLERMO NAVARRO (Scripta, 2024)
For Franco's regime, as for most governments worldwide, stamps were a symbol of sovereignty and carriers of historical and spiritual values because they were an expression of an autonomous national entity. Through its Plan Iconográfico Nacional (National Iconographic Scheme), Franco's regime shaped the image of Spain as shown on postage stamps. The scheme established a series of preferences about what should be - and, therefore, what should not be - on postage stamps. This paper will review the representations on postage stamps of the Catholic Monarchs during Francoism. Due to their direct link with Spain's imperial past, the Monarchs were essential and emblematic characters of Franco's dictatorial regime, which used them as reminders to the Spanish people of the most glorious period of Spain's history. This strategy was meant to provide historical references to legitimize the new state established by Franco in the eyes of public opinion.